Polarised beampattern synthesis against array manifold mismatch. Issue 8 (4th May 2021) - Shi, Shuli; Xu, Yougen; Zhao, Kang; Liu, Zhiwen
Abstract: The problem of joint synthesis of spatial power pattern and mainlobe radiation polarisation using a vector antenna array is considered in the presence of array manifold errors. A general approach to the synthesis problem is to formulate the restriction on the power and radiation polarisation as a convex optimisation programing. However, for certain types of vector antennas like tripole and electromagnetic vector sensors, the optimal weights might be extremely large and the resultant beampattern could be very sensitive to the array manifold errors. An intuitive explanation on this phenomenon is given based on the subspace theory. A worst case performance optimisation technique‐ based scheme is presented to draw attention to the polarised beampattern synthesis against the large weights problem and array manifold errors. Numerical examples regarding different types of vector antennas used for one‐ and two‐dimensional polarised beampattern synthesis are provided to validate the efficacy of the scheme.